P15 Using in situ simulation to direct a quality improvement project (QUIP) in the emergency department. (5th November 2017) - Ward, Catherine
Abstract : Introduction: Emergency Medicine trainees repeatedly cite 'Paediatric Emergencies' as an area of the curriculum they feel less confident in, and would appreciate further training directed towards. Thankfully, despite children making up a significant proportion of overall attendees to general hospital A and E departments, life-threatening events are rare. However, when they do occur unfamiliarity and often-limited previous exposure can act as a barrier to efficient and safe care. The rarity of these presentations leads to sparse opportunities for practical management experience amongst junior staff, and in turn, the identification of the exact areas quality improvement projects should be directed. To overcome this barrier in-situ departmental simulation of a chosen presentation was used. Method: Anaphylaxis was identified, via short survey, as a rare paediatric emergency presentation, which none of the current doctors on the department junior rota had encountered previously. They were also asked about their confidence in managing the presentation. The condition itself requires rapid recognition and treatment, with the potential for inaccurate drug dosing. As this is a relatively rare presentation, to elicit the main obstacles to delivering time critical, safe patient care, clinical scenarios, involving children of varying ages were developed. Doctors from the junior rota each undertook a scenario in a simulated environment, the paediatric resuscitation bay, as it would usually be set up. Time was recorded from anaphylaxis recognition to appropriate treatment. The doctor expected to independently locate, draw up and administer medications. Post scenario participants were asked which areas of practical management they found most challenging. Scenarios were repeated, each doctor assigned to a different scenario, with the availability of a 'paediatric anaphylaxis box'. This contained the algorithm, age-related dosages, drugs and suitably sized syringes to allow accurate dosing and administration. Box contents were determined by the participants' answers in regards to difficulties experienced. Results/Discussion: Use of the box significantly improved the time to drugs administration and ensured the correct dosage administration. Participants, through post event survey completion, unanimously indicated they found it easier to ensure and administer correct dosing using the box, as well as reporting improved confidence in managing the presentation following simulation. Conclusion: The use of simulation in replicating rare presentations, all though not a substitute for practical experience, can increase confidence in management and provide learning opportunities amongst trainees. In addition, allowing the identification of areas to target QuIPs. This could be extrapolated to further rare presentations in both children and adults.